THE ROUTLEDGE HANDBOOK OF ENGLISH-MEDIUM INSTRUCTION IN HIGHER EDUCATION - Bolton, Kingsley; Botha, Werner; Lin, Benedict Tzer Liang (Routledge handbooks in linguistics, 2024)
This handbook discusses the theoretical and disciplinary background to the study of English-medium instruction (EMI) in higher education worldwide. It highlights issues relating to EMI pedagogy, varying motivations for EMI education, and the delivery of EMI in diverse contexts across the world. The spread of English as a teaching medium and the lingua franca of the academic world has been the subject of various debates in recent years on the perceived hegemony of the English language and the 'domain loss' of non-English languages in academic communication. Encompassing a wide range of contributions to the field of EMI, the chapters of this handbook are arranged in four distinct parts: Part I provides an overview of English-medium instruction in higher education worldwide; Part II focuses on EMI in Europe; Part III on EMI in the Middle East, North Africa and Sub-Saharan Africa; and Part IV on EMI in the Asian region. The overall scope and level of expertise of this handbook provides an unrivalled authoritativeness on this field of education. It serves as an essential reference for many courses dealing with applied linguistics, English language education, multilingualism, sociolinguistics and related subjects at many levels of education, including Master's and PhD level studies. A valuable edition for university libraries across the world, and an essential read for many faculty, undergraduate and postgraduate students, educators, and policy makers.